Development of Interactive Digital Learning Based Liveworksheets to Improve Critical Thinking on Respiratory System For High School Student - Qoyum Amalia; Rasyidah Rasyidah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The rapid advancement of information and communication technology demands innovative instructional strategies that foster 21st-century skills, particularly critical thinking. However, biology learning in schools remains predominantly conventional and lacks the integration of scientific-based digital media. The scientific approach and the Liveworksheets platform have become relevant tools as they support active, structured, and inquiry-based learning. This study aims to develop interactive digital student worksheets using the scientific approach by the Liveworksheets platform on the human respiratory system topic for the second grade students at Sinar Husni Helvetia Private High School. Methodology: Employing the Research and Development (R&D) method, this study adopted the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Findings: The validation results show the worksheets is highly valid, with scores of 88.33 % (media), 87.5 % (content), and 87.5 % (assessment). Practicality tests showed an average of 92 % indicating the liveworksheets is highly practical, with student responses (85 %) and teacher responses (93 %). Effectiveness tests demonstrated a significant improvement in students' critical thinking skills, with the average pre-test score of 47 increasing to 86.23 in the post-test, and an N-Gain score of 0.76, categorized as high. Data analysis was conducted quantitatively using percentage and N-Gain calculations. The novelty of this research lies in the direct integration of the scientific approach into the Liveworksheets platform in the form of a digital worksheets that systematically guides students through scientific stages. Contribution: The results of this development enrich the alternatives for valid, practical, and effective digital learning media that support critical thinking skills and reinforce technology-integrated biology learning at the high school level